Intersecting Identities: Exploring Worker-Member Perspectives on Government-Certified Worker-Run Social Cooperatives in South Korea - Claassen Casper Hendrik; Bidet Eric; Jeong Bok Gyo; Kim Junki; Choi Yeanhee (Nonprofit Policy Forum, 2025)
The emergence of state-sanctioned worker-run social cooperatives as a government-certified social enterprise model in South Korea, functioning simultaneously as worker cooperatives, represents an evolutionary shift in the country’s cooperative movement. Enabled by the enactment of important regulatory frameworks, including the 2006 Social Enterprise Promotion Act and the 2012 Framework Act on Cooperatives, these novel hybrid organizational forms reside at the intersection of traditional worker cooperative and government-certified social enterprise organizational forms. This study uses Q-methodology to assess the perspectives of worker-members, revealing insights into the organizational identities of these cooperatives. Three distinct perspectives emerge: “Pragmatic and Empowered Participative Work-Integrated Social Catalysts,” “Public Sector-Backed, Internally Marginalized Social Contributors,” and “(Partially) Disillusioned Network-Centric Social Contributors.” These perspectives underline the diversity in worker-members’ perspectives on these organizational forms. While some worker-members are content, others express discontent, suggesting the existence of tensions between traditional cooperative principles and these novel state-sanctioned social economy organizations. These findings provide insights into the interface between public sector social economy organization policies and traditional cooperative ideals.